SOLVE 3x - 4y =16 ; 2x - 3y = 10

Given, equations are :

3x – 4y = 16  ...  (1)

2x – 3y = 10  ...  (2)

Multiply equation (1) by 2 and equation (2) by 3, we get

(3x – 4y = 16) × 2 and (2x – 3y = 10) × 3

⇒ 6x – 8y = 32  ...  (3)

⇒ 6x – 9y = 30  ...  (4)

Subtracting equation (4) from equation (3), we get

6x – 8y – (6x – 9y) = 32 – 30

⇒ 6x – 8y – 6x + 9y = 2

y = 2

On putting value of y in (1), we get

  • 6

Y=4 X11

  • -2

 3x - 4y = 16 

 2x - 3y = 10

Multiplying equation 1 with 2 and equation 2 with 3

 =>2(3x - 4y = 16)

     3(2x - 3y = 10)

=> 6x - 8y = 32 ---- (iii equation)

      6x - 9y = 30 ------(iv equation)

subtracting iv equation from iii equation

 =>      6x - 8y = 32 ---- (iii equation)

 (-)      6x - 9y = 30

                y = 2

substituting the value of y in ii equation

2x - 3(2) = 10

2x - 6 = 10

2x=16

x = 16/2

x =  8

  • 0
What are you looking for?